Insights into the importance of ecosystem services to human well-being in reservoir landscapes - Jones, S.K.; Boundaogo, M.; DeClerck, Fabrice A.J.; Estrada-Carmona, Natalia; Mirumachi, N.; Mulligan, M. (Elsevier, 2019)
Smallholder farmers in West Africa use multiple ecosystem services (ES) in their day-to-day lives. The contribution that these services make to human well-being (HWB), and therefore to development outcomes, is not well understood. We analyse smallholder farmer perceptions of ES, ecosystem disservices (ED), and their HWB importance around community-managed reservoirs in four semi-arid landscapes in West Africa, using participatory mapping, focus groups and face-to-face surveys. Farmers identified what nature-based benefits (ES) and problems (ED) they perceived across each landscape and rated the importance of each service and disservice for their HWB. Our results indicate that ES make an important contribution to HWB in our study sites. More than 80% of farmers rated benefits from plant-based foods, domestic and agricultural water supplies, biofuel, medicinal plants, and fertile soil, and problems associated with human disease vectors, as of high or very high importance for HWB. Multiple ES were identified as contributing to each dimension of HWB, and ED as detracting from health and material well-being. Perceptions of the importance of several ES and ED varied significantly with socio-economic group, highlighting the need for careful consideration of trade-offs between HWB outcomes and stakeholders in ecosystem management decisions to support sustainable development.